Meningkatkan Kapasitas Staff Biro Umum Dan Administrasi Sekretariat Daerah Provinsi Papua - Jitmau, Gerzon (Journal of Comprehensive Science, 2025)
This study aims to identify the factors that cause the suboptimal performance of staff in the General and Administration Bureau of the Regional Secretariat of Papua Province and formulate a strategy to increase their capacity. The methodology used is a qualitative approach through in-depth interviews, Focus Group Discussions (FGD), participatory observation, and document analysis. The results of the study show that the main obstacles include low work discipline, lack of motivation, lack of training, and rigid bureaucratic structure. The recommendations submitted include strengthening competency-based training, improving the incentive system, and creating a work environment that is more supportive of innovation and staff professionalism development.